Prion protein and Shadoo are involved in overlapping embryonic pathways and trophoblastic development. - Bruno Passet; Rachel Young; Samira Makhzami; Marthe Vilotte; Florence Jaffrezic; Sophie Halliez; Stéphan Bouet; Sylvain Marthey; Manal Khalifé; Colette Kanellopoulos-Langevin; Vincent Béringue; Fabienne Le Provost; et al. (PLoS ONE, 2012)
The potential requirement of either the Prion or Shadoo protein for early mouse embryogenesis was recently suggested. However, the current data did not allow to precise the developmental process that was affected in the absence of both proteins and that led to the observed early lethal phenotype. In the present study, using various Prnp transgenic mouse lines and lentiviral vectors expressing shRNAs that target the Shadoo-encoding mRNA, we further demonstrate the specific requirement of at least one of these two PrP-related proteins at early developmental stages. Histological analysis reveals developmental defect of the ectoplacental cone and important hemorrhage surrounding the Prnp-knockout-Sprn-knockdown E7.5 embryos. By restricting the RNA interference to the trophoblastic cell lineages, the observed lethal phenotype could be attributed to the sole role of these proteins in this trophectoderm-derived compartment. RNAseq analysis performed on early embryos of various Prnp and Sprn genotypes indicated that the simultaneous down-regulation of these two proteins affects cell-adhesion and inflammatory pathways as well as the expression of ectoplacental-specific genes. Overall, our data provide biological clues in favor of a crucial and complementary embryonic role of the prion protein family in Eutherians and emphasizes the need to further evaluate its implication in normal and pathological human placenta biology.